Brief overview of the polymorphism analysis of genes affecting pig prolificacy (LEP, PRLP, ESR BF, EGF, FSH-β, H2A.Z) - Baginé Hunyadi, Ágnes; Balogh, Péter; Kusza, Szilvia (Acta Agraria Debreceniensis, 2015)
Researches are being performed around the world to increase swine prolificacy by using marker-assisted selection (MAS). The present study processes researches of polymorphism examinations on 7 genes. The result of the experiments showed that the leptin gene (LEP) prolactin receptor gene (PRLP), estrogen receptor gene (ESR), properdin B (BF) epidermal growth factor (EGF), follicle-stimulating beta gene (FSH-ß) and Z member of the H2A histon family gene (H2A.Z) and their alleles have a positive effect on reproductive characteristics of different swine breeds. In addition to this, leptin gene (LEP) influences the build, meat production and growth of body fat. Further studies are concerned with the polymorphism of an increasing number of genes, which enables a faster genetic development of swine breeding.